Matteson & McConnell's gerontological nursing : concepts and practice - Linton, Adrianne Dill.; Lach, Helen W.; Matteson, Mary Ann.; McConnell, Eleanor S. (Philadelphia : Saunders, an imprint of Elsevier, 2007)
Matteson & McConnell's Gerontological Nursing, 3rd Edition provides comprehensive, research-based information on nursing care of older adults. Beginning with the basics, the text uses a systems approach to describe the aging process from wellness to illness. It also describes physiological and psychological aspects of aging in detail, as well as assessment and practice in all settings using the nursing process.
Introduction to practice in gerontological nursing. Gerontological nursing: issues and trends in practice / Helen W. Lach. Assessment: focus on function / Helen W. Lach & Carrie M. Smith. Tools for screening and assessment / Helen W. Lach & Carrie M. Smith. Application of nursing theory / Helen W. Lach. Evidence-based practice / Marita G. Titler & Jane Hsiao-Chen Tang. Gerontology: the study of aging / Helen W. Lach. Pharmacological considerations / Adranne Dill Linton. Nutritional considerations / Anna J. Biggs. Ethical considerations / Kathleen T. Lucke -- Aging changes and health deviations. Integument system / Adrianne Dill Linton. Musculoskeletal system / Adrianne Dill Linton. Cardiovascular system / Mary Ann House-Fancher & Ronald J. Lynch. Respiratory system / Adrianne Dill Linton. Neurological system / Pamela Millsap. Gastrointestinal system / Adrianne Dill Linton. Genitourinary system / Adrianne Dill Linton. Endocrine system / Adrianne Dill Linton, Lisa J. Hooter, & Coleen R. Elmers. Immune system / Adrianne Dill Linton. Age-related changes in the special senses / Adrianne Dill Linton. -- Psychosocial aging. Age-related psychological changes / David W. Carroll & Adrianne Dill Linton. Age-related sociological changes / Cheryl Lyn Zukerberg & Adrianne Dill Linton. End of life care of the older adult / Pamela Z. Cacchione & Patrick J. Cacchione -- Competencies and roles in gerontological nursing. Leadership skills / Nina Tumosa & Helen W. Lach. Therapeutic groups for older adults / James H. Cook, Jr. & Candace M. Ball. Team work: interdisciplinary geriatric care / Helen W. Lach. Case management / Todd M. Ruppar. Health promotion and health education for older adults / Helen W. Lach. Quality improvement / Carolyn D. Philpot ... [et al.] -- Gerontological nursing in the context of care. The geriatric continuum of care / Susan A. Ruzicka. Community care / Mary Z. Dunn. Assisted living care / Cheryl Lyn Zukerberg. Acute care / Maria B. Carroll. Subacute care / Elizabeth A. Capezuti -- Long-term care / Adrianne Dill Linton & Helen W. Lach.
Includes bibliographical references and index.
Keywords: Geriatric nursing; Geriatric Nursing; Aging -- physiology